2016
DOI: 10.5306/wjco.v7.i1.87
|View full text |Cite
|
Sign up to set email alerts
|

Overview, prevention and management of chemotherapy extravasation

Abstract: Chemotherapy extravasation remains an accidental complication of chemotherapy administration and may result in serious damage to patients. We review in this article the clinical aspects of chemotherapy extravasation and latest advances in definitions, classification, prevention, management and guidelines. We review the grading of extravasation and tissue damage according to various chemotherapeutic drugs and present an update on treatment and new antidotes including dexrazoxane for anthracyclines extravasation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
149
1
32

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(197 citation statements)
references
References 50 publications
1
149
1
32
Order By: Relevance
“…In this sense, the construction and application of protocols and policies that emphasize such behaviors becomes essential in clinical practice. 19 Regarding the knowledge of the protocol of institutional extravasation, 87.5% of the participants claimed that they knew it, contradicting the results found. The protocols contribute to the standardization of actions for certain events, proving to be a managerial tool of great impact and maintenance of the quality of the care provided.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…In this sense, the construction and application of protocols and policies that emphasize such behaviors becomes essential in clinical practice. 19 Regarding the knowledge of the protocol of institutional extravasation, 87.5% of the participants claimed that they knew it, contradicting the results found. The protocols contribute to the standardization of actions for certain events, proving to be a managerial tool of great impact and maintenance of the quality of the care provided.…”
contrasting
confidence: 56%
“…17 The importance of the knowledge regarding the use of hot compresses, in cases of extravasation by drugs like Vincristine and Vimblastine, is given since this technique can contribute to the reduction of tissue damages, since the heat causes the vasodilation and contributes to the absorption of the minimizing its damage. 19 Also as part of the treatment pipeline, there is the extension of care at home, and the professional of the Nursing team should provide all guidance to the individual, family and caregivers on how to proceed. Thus, it was observed that all professionals showed that avoiding sun exposure is a correct orientation; and 93.7% indicate the demand of the health service in the face of the appearance of blisters, ulcerations or necrosis.…”
mentioning
confidence: 99%
“…The data collection instrument was a structured questionnaire developed by the authors, based on the search for relevant, updated national and international literature, 3,[10][11][12] divided into the following two parts: 1) Questions about the characterization of individuals (sex, age, undergraduate studies, specialization, Master's degree, length of time working in oncology and chemotherapy, training for extravasation, number of jobs and weekly working hours); and 2) Test of knowledge with multiple choice questions, when respondents had to choose a correct answer among the alternatives given. Questions were about the classification of antineoplastic drugs, signs and symptoms of extravasation, main risk factors for extravasation, factors that influence the severity of extravasation, preventive actions, sequence of areas for peripheral venipuncture, care provided when extravasation occurs, and application of cold and hot compresses after extravasation, according to the antineoplastic drug.…”
Section: Methodsmentioning
confidence: 99%
“…The World health Organization (WHO) indicates that 27 million incident cases and nearly 17 million deaths due to cancer are expected to occur in 2030. In Brazil, estimates point to the occurrence of 600,000 new cases of cancer in 2016. Which means that this disease is an important cause of mortality, representing a great public health problem.…”
Section: Introductionmentioning
confidence: 99%
“…Although chemotherapy is considered one of the most effective approaches to treat cancer, it might kill, alongside the malignant cell, any normal cell that grows fast, which, in turn, may result in serious damage to patients [7][8][9]. Most of the chemotherapeutic drugs work by impairing cell division by various mechanisms including damaging DNA and inhibition of the cellular machinery involved in cell division [10].…”
Section: Introductionmentioning
confidence: 99%